Implementation of English Learning Curriculum for Deaf Students - Bedah; Purnama Rika Perdana; Reza Fandana (LPPM Universitas Pekalongan, 2025)
This study discusses the implementation of the English learning curriculum for children/students with special needs, especially students with hearing impairments at Dian Bahagia School. This study aims to explore the application of the curriculum, the challenges faced by teachers, and effective learning methods. The research method used is qualitative, with data obtained through in-depth interviews and observations. The results of the study show that the implementation of a flexible curriculum, such as the Independent Curriculum, plays an important role in meeting the unique needs of Deaf Students. Adjustments in learning methods, such as the use of visual media and a project-based approach, help students understand the material despite having limitations in hearing and verbal communication. The main challenges faced by teachers include students' limitations in pronunciation, text comprehension, and writing skills. The use of visual media, hearing aids, and sign language are the main solutions to overcoming this challenge. Project-based learning methods are effective in improving students' understanding of the material; while encouraging their active involvement in the learning process. The study also emphasizes the importance of collaboration between schools, teachers, parents, and education experts to create inclusive learning programs. In addition, technology, such as sign language translation applications and interactive modules can make a significant contribution to more optimal learning outcomes. The study concludes that the flexibility of the curriculum tailored to students' needs focuses not only on academic achievement; but also on the development of relevant life skills. With this approach, a more inclusive learning environment is created and supports the holistic development of deaf students. Recommendations for further research include exploring the adaptation of project-based learning methods to other specific needs and the application of new technologies in supporting learning.